Striving to Teach Versus Modern Realia - Anzhela Nikishyna (Educational Challenges)
There have always been challenges confronting both teachers and students in the process of sharing knowledge and skills. The purpose of the article is to analyze the situation that has become even more demanding due to the changes connected with the implementation of distance learning.